The Performance Gap in Sport Can Help Determine Which Movements Were Most Essential to Human Evolution - Carroll, Collin (Frontiers in Physiology, 2019)
Men outperform women at sports which require muscular strength and endurance, but the magnitude of this performance gap does not appear to be constant; that is, the performance gap between men and women is greater in some sports than it is in others. Here we examine the size of this gap within the realm of track and field by comparing the top 50 world-record performances of men to the top 50 records set by women in a number of long-distance running, medium-distance running, short-distance running, and jumping events. While women perform at a level ranging from 84.3% to 92.3% of the level at which men perform, the magnitude of the performance gap trends up or down depending on the event. Jumping events exhibit a larger gap between the sexes than running events, and short-distance running events show a smaller disparity between the sexes than do medium- or long-distance running events. This difference suggests that general sexual dimorphism does not explain why female performance is relatively closer to male performance at some track and field events than others. We hypothesize that this trend can be explained by the presence of sex-blind musculoskeletal adaptions, which accumulate over generations to reduce the size of the performance gap in certain movements. We conclude that the selection trend favoring sex-blind musculoskeletal adaptations in humans should be explored further to determine whether the performance gap in sport can indeed be used to determine movements to which the human body is adapted.